The SNX-PX-BAR family in macropinocytosis: the regulation of macropinosome formation by SNX-PX-BAR proteins. - Jack T H Wang (Public Library of Science (PLoS), 2010)
Background Macropinocytosis is an actin-driven endocytic process, whereby membrane ruffles fold back onto the plasma membrane to form large (>0.2 µm in diameter) endocytic organelles called macropinosomes. Relative to other endocytic pathways, little is known about the molecular mechanisms involved in macropinocytosis. Recently, members of the Sorting Nexin (SNX) family have been localized to the cell surface and early macropinosomes, and implicated in macropinosome formation. SNX-PX-BAR proteins form a subset of the SNX family and their lipid-binding (PX) and membrane-curvature sensing (BAR) domain architecture further implicates their functional involvement in macropinosome formation. Methodology/principal findings We exploited the tractability of macropinosomes through image-based screening and systematic overexpression of SNX-PX-BAR proteins to quantitate their effect on macropinosome formation. SNX1 (40.9+/-3.19 macropinosomes), SNX5 (36.99+/-4.48 macropinosomes), SNX9 (37.55+/-2.4 macropinosomes), SNX18 (88.2+/-8 macropinosomes), SNX33 (65.25+/-6.95 macropinosomes) all exhibited statistically significant (p<0.05) increases in average macropinosome numbers per 100 transfected cells as compared to control cells (24.44+/-1.81 macropinosomes). SNX1, SNX5, SNX9, and SNX18 were also found to associate with early-stage macropinosomes within 5 minutes following organelle formation. The modulation of intracellular PI(3,4,5)P(3) levels through overexpression of PTEN or a lipid phosphatase-deficient mutant PTEN(G129E) was also observed to significantly reduce or elevate macropinosome formation respectively; coexpression of PTEN(G129E) with SNX9 or SNX18 synergistically elevated macropinosome formation to 119.4+/-7.13 and 91.4+/-6.37 macropinosomes respectively (p<0.05). Conclusions/significance SNX1, SNX5, SNX9, SNX18, and SNX33 were all found to elevate macropinosome formation and (with the exception of SNX33) associate with early-stage macropinosomes. Moreover the effects of SNX9 and SNX18 overexpression in elevating macropinocytosis is likely to be synergistic with the increase in PI(3,4,5)P(3) levels, which is known to accumulate on the cell surface and early-stage macropinocytic cups. Together these findings represent the first systematic functional study into the impact of the SNX-PX-BAR family on macropinocytosis.